EFISIENSI PENGGUNAAN INPUT PAKAN DAN KEUNTUNGAN PADA USAHA TERNAK BABI DI KECAMATAN TARERAN KABUPATEN MINAHASA SELATAN - Kojo, Rivo E; Panelewen, V V.J; Manese, M A.V; Santa, Nansi (Universitas Sam Ratulangi, 2014)
ABSTRACTFEED EFFICIENCY AND PROFITABILITY OF PIG FARM AT TARERAN DISTRICT OF SOUTH MINAHASA REGENCY. Tareran district is located in the South Minahasa regency consisted of 12 (twelve) villages and has the area of 7602.45 hectares or 76024.5 Km2. Generally, Tareran community work as farmers. The most pig populations at Tareran district were found at the three villages including villages of Lansot, Rumoong Atas, and Rumoong Atas Dua. The problems of this study are that; first, is the use of production cost in the pig business at the Tareran district efficient? Second, does the production cost provide benefits? Research objectives are to evaluate the type and total cost of production in the pig business at the Tareran district, to analyze the efficiency of input usedin pig farming, and to determine the optimum use of inputs in achieving the business benefits pigs. The research was conducted in the Tareran district of South Minahasa Regency involving the number of 30 breeders as respondents. Data collections were conducted in the period time of 2 months. The data in this study were obtained from two sources of primary and secondary data. Samples were taken using purposive sampling method. The use of this technique was always based on certain characteristics obtained through the population. The results of these studies showed the production cost of pig farm was Rp18.557.038 per period per year with a gain of about Rp 13.611.309 per period per year. Inefficient use of food inputs indicating to the farmers need to reduce feeding cost because it caused cost redundancy. It was known that animal body weight achieved was different for each type of pig. In addition, the use of ration inputs to achieve maximum body weight was also different for each animal.Keywords: Efficiency, Ration Input, Profit, Pig Farm, Tareran District.